IDENTIFICATION OF DIRECTIONS FOR THE APPLICATION OF NEW TEACHING METHODS FOR THE EFFECTIVE ORGANIZATION OF TRAINING - Nijat, Shixalizade; Ulviyya, Nasibova (Revista Gênero e Interdisciplinaridade, 2025)
The effective organization of training is a critical aspect of modern education systems, requiring innovative teaching methods that align with the needs of the XXI century learner. This study explores the application of new teaching methodologies, focusing on their implementation strategies and effectiveness in various educational contexts. By examining a range of pedagogical techniques—including collaborative learning, technology integration, and experiential methods—this paper identifies practical approaches to enhancing teaching efficacy. Findings suggest that adopting diverse and student-centered methodologies significantly improves engagement and learning outcomes.